Allergic rhinitis facts from an Irish pediatric population - Andreea Nae; Colleen B. Heffernan; Michael Colreavy (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2023)
Abstract Objective Assessing the main allergens in the pediatric population from the largest urban area in the country. Methods Clinical letters of patients referred with possible allergic rhinitis (AR) were retrospectively reviewed over the past 5 years. Results Five hundred and fifty‐five patients were included. Males suffer twice as often with AR than females and have high titers of allergens. House dust mites (44.7%) and grass pollen (29%) were the main allergens in our area, with 48% of patients sensitized to both allergens. Half of the patients had the diagnosis of AR confirmed with positive allergen‐specific tests. For the other half, the diagnosis was based on a clinical assessment performed by a pediatric otolaryngologist. Conclusions Half of suspected AR children have environmental allergen sensitivity confirmed by testing, and a large number had a clinical diagnosis of AR after an otolaryngology consultation. Our findings can help clinicians to initiate AR treatment considering the most problematic allergens in the area.